مسببات البخر الفموي- دراسة سريرية - لايقة, عمار; حسن, حازم (Latakia University Journal -Medical Sciences Series, 2019)
يُعدُّ البخر الفموي من المشاكل المهمة التي تواجه طبيب الأسنان بسبب عوامل كثيرة مسببة له. ومن هنا كان الهدف من دراستنا هذه دراسة العلاقة بين البخر الفموي و بين مجموعة من العوامل الموضعية (الجنس، التدخين، عمر المريض، الصحة الفموية) التي يمكن أن تؤثر في البيئة الفموية والتي تؤدي إلى ظهور روائح كريهة من الفم. استخدمنا في دراستنا عينة مكونة من (1450) مراجعاً إلى كلية طب الأسنان، وذلك بهدف دراسة انتشار البخر الفموي لديهم . لقد تم التأكد من أن هناك علاقة متناسبة طردياً بين البخر الفموي و تقدم العمر، بينما لم يكن هناك تأثيراً مهماً للجنس على انتشار البخر الفموي. إن قلة العناية بالصحة الفموية، فضلاً عن عامل التدخين مسببات أثبت دورهما بوصفهما عاملين مهمين في زيادة احتمال ظهور البخر الفموي. Because of the numerous factors causing it, halitosis (oral malodor) is considered one of the most important problems facing dentists nowadays. The aim of this research is to study the relationship between halitosis and a group of local factors (sex, smoking, patient age, oral care) which can affect the oral environment causing the emergence of what is called oral malodor. In this study, We have chosen 1450 outpatients of the Faculty of Dentistry to study the prevalence of halitosis; we have ensured that there is an extreme proportional relationship between halitosis and age advancement, whereas sex has no significant effect on halitosis. We have also proved that both lack of oral care and smoking are important factors in increasing the possibility of halitosis emerging.